Reforming The Authority Of The National Human Rights Commission From A Legal Perspective - Luhukay, Roni Sulistyanto (Universitas Negeri Gorontalo, 2025)
The institutional protection of human rights in Indonesia remains constrained by limited mandates and authority, particularly in the case of the National Commission on Human Rights (Komnas HAM). Unlike similar institutions in other jurisdictions, Komnas HAM lacks prosecutorial power, binding decision-making authority, and sufficient independence to effectively address human rights violations. This research, using a normative legal method, identifies the structural and regulatory limitations of Komnas HAM as the core issue that weakens human rights enforcement in Indonesia. Existing literature has primarily focused on Komnas HAM’s performance without thoroughly analyzing the philosophical and legal justification for enhancing its authority. This study fills that gap by providing a philosophical reflection on the institutional role of Komnas HAM and proposing reform measures based on international best practices. Key findings suggest that strengthening Komnas HAM through expanded authority such as investigatory and prosecutorial powers, binding decisions, oversight of state policies, and greater resource allocation could significantly improve human rights protection. Theoretically, this contributes to discourse on state obligation in human rights enforcement; practically, it offers a concrete institutional reform model to enhance Komnas HAM's role in Indonesia’s legal system.